Modification of Tankring Oven as a Dryer and Sample Storage for Research Activities of Fish Products in Microbiology and Biotechnology Laboratory - Nofriati, Nofriati; Ildawati, Ildawati; Erwanti, Erwanti (Jurnal Perikanan dan Kelautan, 2023)
Ovens or artificial/mechanical drying devices are tools used in educational and research activities in laboratories that function for sterilization, drying, and storing samples or processed products. This research modifies the tangkring oven with an innovative use of electricity. The background of the study is because there is no drying device and small sample storage with a small number of samples. The modification aims to make a replacement device as a dryer and sample storage in the laboratory. This study used an experimental method, and the data were analyzed descriptively. The oven that has been modified using a tangkring oven has an inner dimension of length =36 cm; width=36 cm; height =32 cm, heat source from 150-watt halogen lamps totaling two pieces, and a 12 cm diameter fan, the outer part of the tool has a length = 42.5 cm; width = 38 cm; height = 38 cm, equipped with legs and four wheels with a height = 85 cm. Temperature testing was carried out on each shelf with a thermometer as a temperature measuring instrument, with a temperature range of 30-60⁰C. The time required to reach a constant temperature is 0.5 to 20 minutes, and the temperature difference between the regulated temperature and the temperature achieved on the tool ±2ºC shows the results obtained are still within tolerance, the error value is still within tolerance ±5% indicates the results of the tool system performance is not disturbed. From the observations made, it is concluded that the modified tangkring oven can be used as a drying device and sample storage with a faster time and using limited samples for laboratory activities.